Multifunctionality at the Prairie Dunes Golf Course - Coup, Samuel (Kansas State University, 2023)
Golf courses have been a pressing issue in environmental and land planning studies over the past twenty years. However, while studies have shown that golf courses can have a positive impact, less attention has been paid to the multifunctionality of these courses. This research addresses this issue by examining how multifunctional interventions can happen in North America. More specifically, this study investigates Prairie Dunes Country Club using a mapping experience and scorecard to collect information for this golf course in Hutchinson, Kansas. The primary finding is that Prairie Dunes would benefit from implementing multifunctional interventions in the course. The projective design for these proposed interventions was developed based on a literature review, five precedent studies, a mapping experience, and a suitability analysis completed for the Prairie Dunes Country Club. Finally, a projective design is established to guide the exploration and development of the projective interventions at Prairie Dunes.
Keywords: Multifunctionality; Golf course; Mapping experiences